Introduction: Hong Kong after the reversion: In search of a post‐colonial order - TANG, Tuck Hong James (Institutional Knowledge at Singapore Management University, 1999)
The political handover of Hong Kong on 1 July 1997 turned out to be a non-eventwith little political drama. Emotions ran high when the Union Jack was loweredand was replaced by the Chinese national flag (wuxing hongqi), peacefully endingover one and a half centuries of British colonial rule in Hong Kong. The handovertook place smoothly, despite the heavy rain, without political and social turbulence.The Sino-British disagreement over the abolition of the Legislative Council marredthe occasion, but the swearing-in of a pro-Beijing Provisional Legislative Councilwas largely accepted as a fait accompli.